Practice and methods of developing a reading culture for modern university youth in China (on the Nanchang University example) - Zhang, Ning (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
The problem of reading culture of modern university youth is investigated in two interconnected dimensions. On the one hand, it is interpreted as an obvious socio-cultural challenge of the era of information and communication revolution, actualising the practice of interaction of traditional and modern forms and methods of broadcasting information flows. On the other hand, this problem is illustrated by the history of the development of reading culture by students of Nanchang University which allows us to complete its socio-theoretical analysis with representative empirical studies using the practice of amazing reading culture by students of one of the famous universities of modern China. The habits, preferences, distribution of time and purposes of reading of university youth are described. It is shown that most students have a positive attitude towards reading, but there are such problems as lack of time for reading and lack of reading conditions. The practice of improving the reading culture of students at Nanchang University, including the definition of reading goals, stimulating interest in reading, using traditional culture to improve the level of text content, cultural development, teacher control method, etc. are analysed. The strategies for cultivating cultural confidence, international technologies and media resources, enriching educational resources and reading environment, stimulating internal motivation and individual support, using new ones to develop students’ reading culture are summarised.
Keywords: university youth; reading culture; cultural confidence; digital technologies; media resources; educational resources; Confucian educational traditions